From marches to movements: building and sustaining a social movement following collective action. (October 2020) - Selvanathan, Hema Preya; Jetten, Jolanda
Highlights: Collective action produces social psychological outcomes that help build and sustain a social movement. Participating in collective action can motivate continued involvement by encouraging ingroup identification and well-being. Collective action can shape broader attitudes in polarizing ways depending on features of the protest and public audience. Movement leaders serve to mobilize and unite a diverse group of bystanders into active movement participants. Abstract : Collective action has the potential to have large-scale implications for a society. We review the processes that are key to understanding the path from collective action to the continuation and success of a social movement. First, we consider how the experience of participating in collective action can foster continued commitment to a cause. Next, since gaining broader support from society is key to the success of social movements, we discuss how the very nature of collective action employed can mobilize support or elicit backlash from members of the general public. Finally, we describe the role of movement leaders whose task is to unite movement participants while also mobilizing the broader society to rally behind the cause for social change. Emergent research on the consequences of collective action contributes to our understanding of the dynamic processes involved in maintaining a movement.